Parental knowledge, views, and perceptions of human papilloma virus infection and vaccination-cross-sectional descriptive study - Mansour A. Tobaiqy; Safaa A. Mehdar; Tasneem I. Altayeb; Tala M. Saad; Sulafa T. Alqutub (Journal of Family Medicine and Primary Care)
Human papillomavirus (HPV) is a highly contagious virus that is linked to cervical cancer and is a major public health issue. Saudi Arabia national efforts aimed to have females aged 9-25 years to receive the available vaccine. Objectives: This study aims to explore parental knowledge, views, and perceptions around HPV in Saudi Arabia. Methods: A cross-sectional online questionnaire was used through direct interview to collect information from a group of parents attending King Abdul-Aziz University Hospital in Jeddah, Saudi Arabia. The questionnaire comprised items including demographics, knowledge, views, and perceptions of HPV infection and vaccination. Results: Of the 500 parents who participated in this study, only 54 (11%) had heard about HPV being associated with cervical cancer. The majority of the participants reported being from the middle social class (n = 472, 94.4%). The vast majority (n = 483, 96.8%) had never heard of the HPV vaccine and (n = 470, 94%) were unwilling to vaccinate their daughters. The primary reported reason behind refusing the vaccine was the lack of information on the importance of HPV vaccination (n = 426, 85.2%). The majority (n = 419, 83.8%) believed that there was insufficient information regarding vaccine safety and efficacy. Participants suggested ways to increase vaccination acceptance like social media awareness (n = 369, 73.8%), educational seminars in schools (n = 254, 50.8%), and a governmental platform (n = 218, 43.6%) providing information on HPV infection and promoting vaccination. Conclusion: Parents in the present study demonstrated a substantial lack of knowledge about HPV infection and vaccination, which may necessitate the establishment of national awareness campaigns.